HUBUNGAN ANTARA FREKUENSI KEMOTERAPI DAN STATUS NUTRISI PASIEN KANKER YANG MENJALANI KEMOTERAPI DI RUANG SANJIWANI RSUP SANGLAH DENPASAR - Dewi, Ni Made Ayu Puspa; Nurhesti, Putu Oka Yuli; Damayanti, Made Rini (Coping: Community of Publishing in Nursing; Vol 8 No 3 (2020): Oktober 2020DO - 10.24843/coping.2020.v08.i03.p06, 2020)
Chemotherapy is an effective therapy for cancer management. Repeated chemotherapy can cause various side effects. Side effects that appear after chemotherapy may affect cancer patient’s nutrition status. This study aimed to determine the relationship between chemotherapy’s frequency and nutrition status on cancer patients who underwent chemotherapy in Sanjiwani Room at Sanglah General Hospital, Denpasar. The methods of this study is a retrospective study based on hospital information systems’s medical records. This study had purposive sampling technique and an 80 patients were chosen as sample. This study found that most of cancer patient had low category of chemotherapy’s frequency (1-3 cycle’s of chemotheraphy) (65%) and most of them had ideal nutrition status (BMI 18,5 – 25,0 kg/m2) (73.8%). Spearman Rank correlation test showed that there was a significant relationship between chemotherapy’s frequency and nutrition status on cancer patients who underwent chemotherapy in Sanjiwani Room at Sanglah General Hospital, Denpasar (p value = 0.00; ? = 0,05; r = -0.79). Determinant’s coeffisien’s (R) of this study known as 62,4%. In conclusion, there is strong negative’s correlation between chemotherapy’s frequency and nutrition status which means the more chemotherapy’s frequency makes nutrition status on cancer patients who underwent chemotherapy is less than ideal and vice versa. Most of chemotherapy frequency’s factor may affect patient’s nutrition status.